FemiLISm now!: Identifying and exploring feminist theories and methods in CAIS/ACSI and ASIS&T conference proceedings, 1993-2021 - Allard, Danielle; Oliphant, Tami; Chambers, Thane (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2023)
This paper reports on a systematic literature review of CAIS/ACSI and ASIS&T conference proceedings to identify, analyze, and map the application of feminist theories, methods, and epistemologies across a sample of LIS research. We seek a better understanding of feminist theories in LIS to a) identify how/where it has been taken up (and not taken up); b) identify feminist research themes and influence over time and across subdomains; and c) to consider how to build on intersectional feminist theories and praxis in LIS to move toward a critical intersectional femiLISt movement that is embraced and embedded within our field.